Beyond argumentation: a practice-based approach to environmental policy. Issue 5 (3rd September 2019) - Behagel, Jelle Hendrik; Arts, Bas; Turnhout, Esther
ABSTRACT: We propose that a practice-based approach to environmental policy can help consolidate theoretical understanding of and empirical focus on practices in IPA. Doing so counteracts a tendency to privilege knowledge and discourse in IPA and environmental policy analysis. We draw on multiple strands of practice theory to inform three sensitising concepts: situated agency, logic of practice, and performativity. These concepts provide the analytical tools to investigate how social order and social change originate from the entanglement of meaning and action in practice. We illustrate these concepts by applying them to practices of community forest management in the countries of Ethiopia and Tanzania. Our analysis suggests that a practice-based approach is able to offer nuanced and empirically grounded accounts of political struggles and democratic practices. Its potential is especially strong in cases where policy-making and policy ideas and outcomes are less clearly linked to argumentative processes. We conclude by arguing for further inclusion and consolidation of practice-based approaches within the tradition of interpretive policy analysis.